Penerapan Clean code pada Aplikasi Siizin Berdasarkan Smells and Heuristics - irfan, muhammad; Widhiarso, Wijang; Rachmadi, Muhammad (Universitas Multi Data Palembang, 2024)
This research discusses the application of the Clean code principle to the development of the CodeIgniter 3-based SIIZIN application by applying smells and heuristics analysis. Code smells are found in the Names, Comments, and Generals categories, such as N1: Choose Descriptive Names, C5: Commented-Out Code, C3: Redundant Comment, G5: Duplication, G20: Function Names Should Say What They Do, and G12: Clutter. Through in-depth analysis and application of Clean code principles, it succeeded in improving the readability and efficiency of the code, eliminating duplication, and describing functions according to their names. Not only that, this research also managed to eliminate useless comments to improve code clarity and maintainability. The results of this research are expected to contribute to the maintenance and development of the SIIZIN application, so as to ensure its sustainability and effectiveness in licensing management.